Perempuan, Mahar, dan Stratifikasi Sosial dalam Naskah Peraturan Bimbang dalam Negeri Bangkahulu - Chika Amelia Pektra; Mamlahatun Buduroh (Jumantara: Jurnal Manuskrip Nusantara, 2021)
This study discusses the relationships between women, dowry and social stratification that are reflected in a manuscript on marriage regulations in Bengkulu entitled Peraturan Bimbang dalam Negeri Bangkahulu held in the National Library of Indonesia, with shelfmark Ml.144. This article considers the position of women in the determination of marriage dowry in the Peraturan Bimbang dalam Negeri Bangkahulu manuscript, and aims to describe the relations between women, dowry and social stratification that prevailed in 1882 and to describe the views of Bengkulu society regarding marital regulations. This research was conducted using descriptive analytical methods and literature study techniques and sociological approaches to examine the interrelation of these three elements. The results show that there are binding rules between women, the dowry and social stratification in the Bengkulu Malay community as reflected in the text. The regulation determines the amount of dowry used as a sign or symbol of women's social status in society, and this concept is still valid in the Malay-Bangkahulu community to this day. However, the regulation experienced a shift in the dowry determination. Specifically, the determination of the amount of dowry in the past was based on the lineage owned by women, whereas at present the education and profession of women are the determining factors that are capable of causing changes in social stratification that develops in society.